Prenatal exposure to acid‐suppressive drugs and the risk of allergic diseases in the offspring: a cohort study. Issue 2 (22nd January 2014) - Mulder, B.; Schuiling‐Veninga, C. C. M.; Bos, H. J.; De, T. W.; Jick, S. S.; Hak, E.
Summary Background Recent studies reported increased risks for the development of asthma in children after prenatal exposure to acid‐suppressive drugs. As a result of common pathogenesis, associations could also be present for other allergic diseases. Methods Using the prescription database IADB.nl, we conducted a cohort study amongst 33 536 children in the Netherlands, with a maximum follow‐up of 8 years. Maternal exposure was defined as ≥1 dispensed prescription for proton pump inhibitors (PPIs) and/or Histamine 2‐antagonists (H2As) during pregnancy. Children were considered to have a drug‐treated allergic disease if they received either ≥2 prescriptions for dermal (atopic dermatitis), inhaled (asthma) or nasal (allergic rhinitis) steroids within a 12‐month period. Clustered Cox proportional hazard regression was used to estimate crude and adjusted hazard ratios (aHR) with 95% confidence intervals (95% CI). Results The aHR for the development of any allergic disease was 1.37 (95% CI: 1.14–1.66) for children exposed to PPIs or H2As. Prenatal exposure to PPIs and/or H2As was associated with atopic dermatitis, asthma and allergic rhinitis with aHRs of 1.32 (95% CI 1.06–1.64), 1.57 (95% CI 1.20–2.05) and 2.40 (95% CI 1.42–4.04), respectively. The aHR for the development of two or more (aHR 2.13 95% CI: 1.43–3.19) and three allergic diseases (aHR 5.18 95% CI: 2.16–12.42) were even more elevated after prenatal exposure to PPIs or H2As. Conclusion Prenatal exposure to PPIs and H2As appeared associated with an increased risk for the development of atopic dermatitis, asthma and allergic rhinitis in the offspring, especially with the development of multiple allergic diseases. Because our study has limitations inherent to observational studies, prospective studies are now warranted to confirm our findings.